Spatial aspects of federalism and intergovernmental fiscal relations — From efficiency and distribution to growth - Döring, Thomas (Raumforschung und Raumordnung | Spatial Research and Planning, 2005)
In the last 40 years, in public finance the examination of spatial aspects of federalism and intergovernmental fiscal relations was dominated by allocative and distributional issues. Modern growth theory and complementary approaches lead to a shift in the research perspective. Against this background the paper discusses how the findings of modern growth theory can affect the design of intergovernmental fiscal relations. The results of this analysis can be summarized as follows: (1) the existence of a geographically different growth dynamic provides an additional justification for a decentralization of political competences. (2) To cover more exactly the regional economic backward and forward linkages, especially local government authorities should intensify their cooperative behavior. (3) From the perspective of economic growth, the equalizing effect of horizontal transfers between decentralized jurisdictions should be limited.